cato encodes a basic helix-loop-helix transcription factor implicated in the correct differentiation of Drosophila sense organs. - Goulding, S.E.; White, N.M.; Jarman, A.P. (Developmental Biology, 2000)
In Drosophila neurogenesis, proneural genes encode bHLH proteins that are required for neural precursor selection. But many vertebrate homologues are expressed later and are postulated to have multiple roles during neurogenesis. We have isolated a new Drosophila gene, cato, which encodes a protein with a bHLH domain that is closely related to that of the proneural protein Atonal. cato expression is restricted to the developing PNS, where it is expressed in between the stages of precursor selection and terminal differentiation (and therefore later than the proneural genes). We present evidence from loss-of-function and misexpression experiments that cato is involved in sensory neurone morphology. Moreover, in prospero mutants, in which axon and dendrite outgrowth is defective, cato is strongly derepressed in the developing CNS.